2015
DOI: 10.1111/mec.13264
|View full text |Cite
|
Sign up to set email alerts
|

Formalizing the definition of meta‐analysis in Molecular Ecology

Abstract: Meta-analysis, the statistical synthesis of pertinent literature to develop evidence-based conclusions, is relatively new to the field of molecular ecology, with the first metaanalysis published in the journal Molecular Ecology in 2003 (Slate & Phua 2003). The goal of this article is to formalize the definition of meta-analysis for the authors, editors, reviewers and readers of Molecular Ecology by completing a review of the meta-analyses previously published in this journal. We also provide a brief overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…However, the nonrandom distribution of genetic diversity in these systems may have a strong influence on the ability of populations to adapt to local conditions (Kawecki & Holt 2002). We hence believe that the time is ripe to make a valuable use of the large amount of data that has been collected in the last decades in population genetics, so as to transform a collection of independent case studies into general rules (ArchMiller et al 2015). As describing and understanding the patterns of biological diversity is one of the bases of integrative and efficient conservation measures (Chave 2013), this should become a priority for population and conservation geneticists.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nonrandom distribution of genetic diversity in these systems may have a strong influence on the ability of populations to adapt to local conditions (Kawecki & Holt 2002). We hence believe that the time is ripe to make a valuable use of the large amount of data that has been collected in the last decades in population genetics, so as to transform a collection of independent case studies into general rules (ArchMiller et al 2015). As describing and understanding the patterns of biological diversity is one of the bases of integrative and efficient conservation measures (Chave 2013), this should become a priority for population and conservation geneticists.…”
Section: Discussionmentioning
confidence: 99%
“…When proper analytical treatment is applied, meta-analyses are powerful analytical tools to decipher the structure and ecology of microbial communities (ArchMiller et al, 2015). When analyzing the global microbial eukaryotic diversity in freshwaters, using the same dataset as in our study, Debroas et al (2017) showed that fungi represented 17% of this diversity.…”
Section: Fungal Communities In Freshwater Habitatsmentioning
confidence: 60%
“…; Koricheva & Gurevitch ; ArchMiller et al . ). In our paper, we have described how nonindependence can affect the calculation of effect size statistics, and result in correlations among effect size estimates.…”
Section: Conclusion and Recommendationsmentioning
confidence: 97%
“…; Koricheva & Gurevitch ; ArchMiller et al . ), suggesting a major under appreciation of its potential impact on study conclusions.…”
Section: Nonindependence and The Role Of Sensitivity Analysesmentioning
confidence: 99%